Pavement condition sensor based on a dual optical frequency comb generator. (November 2022) - Ruiz-Llata, Marta; Lombana, Marco A.; Bonilla-Manrique, Oscar E.; Acedo, Pablo
Highlights: Mobile pavement condition sensor based on diffuse reflectance near infrared spectroscopy. Sensor based on an optical frequency comb generator. Remote sensor taking advantage of dual comb detection method. Fast measurement of pavement spectral information to detect water and ice on its surface. Abstract: A pavement condition sensor aims to estimate the pavement surface grip, and therefore the sensor must detect the presence of water, snow, slush or the like on the surface of the pavement. The leading technology for such a sensor is near infrared diffuse reflectance spectroscopy using a wavelength range around a water absorption peak. In this paper we present a pavement condition sensor based on said technique that uses an electro-optic dual optical frequency comb generator as optical source. The proposed sensor provides unique properties in terms of measuring integration time that are necessary to advance the pavement condition several meters ahead of a moving vehicle.